2020
DOI: 10.1186/s13046-020-01696-7
|View full text |Cite
|
Sign up to set email alerts
|

NUCKS promotes cell proliferation and suppresses autophagy through the mTOR-Beclin1 pathway in gastric cancer

Abstract: Background Nuclear casein kinase and cyclin-dependent kinase substrate (NUCKS), a novel gene first reported in 2001, is a member of the high mobility group (HMG) family. Although very little is known regarding the biological roles of NUCKS, emerging clinical evidence suggests that the NUCKS protein can be used as a biomarker and therapeutic target in various human ailments, including several types of cancer. Methods We first assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 54 publications
1
21
0
Order By: Relevance
“…The effects of the PI3K/Akt pathway in cancer cell cycle process, survive, metabolism, motility and the tumor angiogenesis and inflammatory cell recruitment have been well established [23,24]. Some studies have reported that NUCKS regulates gastric cancer cell proliferation and apoptosis though PI3K/AKT/mTOR signalling pathway [7,21]. In the present study, the phosphorylation of PI3K and AKT were suppressed by NUCKS knockdown compared with that in si-NC group in A549 cells.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The effects of the PI3K/Akt pathway in cancer cell cycle process, survive, metabolism, motility and the tumor angiogenesis and inflammatory cell recruitment have been well established [23,24]. Some studies have reported that NUCKS regulates gastric cancer cell proliferation and apoptosis though PI3K/AKT/mTOR signalling pathway [7,21]. In the present study, the phosphorylation of PI3K and AKT were suppressed by NUCKS knockdown compared with that in si-NC group in A549 cells.…”
Section: Discussionsupporting
confidence: 48%
“…The chromosomal protein nuclear ubiquitous casein and cyclin-dependent kinases substrate (NUCKS) is a highly phosphorylated protein that is similar to the high-mobility group protein family and is involved in the tumorigenesis of various human malignancies [6,7]. In addition, NUCKS overexpression has been reported in numerous cancers and has been shown to enhance tumor cell viability and invasion [7][8][9]. However, its role in the progression of lung cancer is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…ere is growing evidence that the mTOR signaling pathway plays an important role in the occurrence and development of many malignant cancers [39][40][41][42][43][44], including lung, breast, stomach, and liver cancer. mTOR is a key regulatory factor in the initiation stages of autophagy and functions as a negative regulatory molecule of autophagy, so that its activation inhibits autophagy [45].…”
Section: Discussionmentioning
confidence: 99%
“…Puromycin (2 mg/mL) was used to select successfully transfected cells. Lentiviral production, infection, and establishment of stable human gastric cancer cell lines with the overexpression of the MET gene were performed as previously described [23,24].…”
Section: Transfection and Infectionmentioning
confidence: 99%